Automated image analysis of seedlings for vigor evaluation of common bean seeds (Acta Scientiarum. Agronomy, 2014)
Quickly and precise evaluations of the vigor of seeds are highly desirable for the success of quality control programs applied to the seed industry. The objective of this experiment was to determine the number of days necessary to calculate the vigor index of common bean seeds using an automated system of seedling images (SVIS®), and compare its results with the traditional tests of seed vigor. Samples of five seed lots of the IAC Carioca cultivar were submitted to germination, accelerated aging, seedling emergence in sand and electrical conductivity tests. The parameters measured by the Seed Vigor Imaging System (SVIS®) were mean seedling length, growth (ratio of the actual seedling growth to the maximum possible growth), uniformity of growth and the vigor indexes 30:70, 40:60, 50:50, 60:40 and 70:30 (based on different growth/uniformity ratios), and computed from scanned images of three- and four-day-old seedlings.  Results of SVIS® analyses were consistent with the physiological potential evaluations provided by the traditional tests of seed vigor. Therefore, the SVIS® is efficient for detecting differences in vigor among seed lots of common bean (IAC Carioca cultivar) using three- or four-day-old seedlings, independently of the growth/uniformity ratios used to calculate the vigor index.